PENGARUH PENDAPATAN ASLI DAERAH (PAD), DANA PERIMBANGAN TERHADAP PERTUMBUHAN EKONOMI DAN KEMISKINAN DI KABUPATEN MIMIKA - Rulan L Manduapessy (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
The purpose of this study is to determine the effect of original local government Revenue (PAD) on economic growth in Mimika Regency, to determine the effect of balancing funds on economic growth in Mimika Regency, to determine the effect of original local government Revenue (PAD) on poverty in Mimika Regency. balance funds on poverty in Mimika Regency, and to determine the effect of economic growth on poverty in Mimika Regency.The analytical tool used in this research is path analysis with a multi-indicator method called structural equation modeling (SEM). The results of the study indicate that the original local government Revenue (PAD) has a negative and significant effect on economic growth in Mimika Regency, the balance funds have a positive and significant effect on economic growth, PAD has a positive and significant effect on the poverty level, the balance funds have a negative and significant effect on economic growth, economic growth has a positive and significant effect on poverty levels